Engineering pervasive services for legacy software - Gordillo, Silvia Ethel (^p Datos electrónicos (1 archivo : 306 KB))
In this paper we present a novel architectural approach to engineer applications that provide location-aware services; in particular, we explain how to extend existing software systems with location-aware services. We show how a clear separation of design concerns (e.g. applicative, context-specific, etc) helps to improve modularity. We stress that, by using dependency mechanisms among outstanding components, we can get rid of explicit rule-based expressions thus simplifying evolution and maintenance. We first motivate our research with a simple example. Next, we present the big picture of our architectural approach. Then we detail how to specify location-aware services; we present details of the services’ activation mechanisms. We finally we discuss some related work in the field. We conclude with some further issues in which we are now working.